1997
DOI: 10.3109/00016359709091937
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries on adjacent approximal tooth surfaces in relation to order of eruption

Abstract: The occurrence of dental caries on adjacent approximal molar and premolar tooth surfaces was examined on posterior bitewing radiographs. More distal surfaces of the first permanent molars were decayed than adjacent mesial surfaces of the second molars. The appearance of dental caries on adjacent premolar surfaces was related to the order of eruption; the surface that had erupted first was likely to be decayed first. Reports from other studies on adjacent approximal surfaces indicate that this conclusion has a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
(2 reference statements)
2
7
0
Order By: Relevance
“…One can only speculate about such possible differences. According to the present and previous results (4–6, 14), it seems that the ‘oldest’ tooth surface may be at a ‘disadvantage’ in that it is more readily affected by caries progression up to a radiographically visible stage. Thus, the so‐called post‐eruptive maturation of the enamel does not seem to be an advantage for preventing caries on the approximal surfaces.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…One can only speculate about such possible differences. According to the present and previous results (4–6, 14), it seems that the ‘oldest’ tooth surface may be at a ‘disadvantage’ in that it is more readily affected by caries progression up to a radiographically visible stage. Thus, the so‐called post‐eruptive maturation of the enamel does not seem to be an advantage for preventing caries on the approximal surfaces.…”
Section: Discussionsupporting
confidence: 60%
“…As judged clinically, neighbouring approximal tooth surfaces differ in their caries susceptibility (3–6), implying that one surface may show obvious radiographic signs of caries while the neighbouring surface does not. Various reasons for the differing caries susceptibility have been proposed, such as different tooth surface morphology or different post‐eruptive enamel maturation of the surfaces (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 The most frequent sites of attack are the occlusal surfaces of the first and second permanent molars. 4 In addition, it was reported that neighboring approximal tooth surfaces differ in their caries susceptibility, [5][6][7] implying that one surface may show obvious radiographic signs of caries, while the neighboring surface does not. 8 Various reasons for the differing caries susceptibilities have been proposed, such as different tooth surface morphology or different posteruptive enamel maturation of the surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1940s, a number of studies have described the relative susceptibility of teeth to carious attack (10)(11)(12)(13)(14)(15)(16)(17)(18); however, each of these studies has had some notable limitations. Most of the studies focused on the susceptibility of only tooth surfaces, all used relatively small target populations, and none replicated Klein and Palmer's original analytical methods.…”
mentioning
confidence: 99%